Proposta de modelo para avaliação da maturidade DevOps: estudo de caso em empresas de grande porte - Levita, Carlos de Amorim (2017)
This work aims to identify how large organizations that use DevOps approach structure themselves to achieve agility in applications deployment. For this purpose, a case study was performed in companies that are using techniques to enable the DevOps approach implementation. This is a key initiative to address the new digital business requirements at the speed currently needed by internal users and clients, while keeping the controls required by Information Technology. To better understand the DevOps movement, this research aimed to map the main DevOps practices, based on literature review, in order to outline a theory that demonstrates its use. Furthermore, it was also intended to present a DevOps maturity assessment model, based on questions with structured answers about each of the previously described practices. The fieldwork methodology was based on a case study, in order to apply the DevOps maturity assessment model that was developed. As a result, a detailed description was presented, with the path chosen by each company to implement the DevOps practices in the IT department. After that, a comparative analysis was made between the researched cases to show possible improvement points, indicated by means of the notes achieved with the use of the DevOps maturity assessment model. The conclusion allowed to highlight two practical paths for IT reorganization, proven by the field research, in order to successfully implement a joint approach of DevOps practices and agile methodology for application development